Avaliação físico/química e microbiológica das águas bruta e tratada destinada ao consumo humano do município de Pedro Afonso –Tocantins - Miranda, Maria Isabel (Universidade Federal do Tocantins, 2016)
The water resources both in surface as underground have often been contaminated by organic and inorganic substances at levels that compromise its most noble uses, such as public supply.This contamination is mainly because of the intensive use of agrochemicals in agriculture and the emerging pollutants, such as pharmaceuticalsthat are introduced into the aquatic environment by sewage without the correct treatment. This research had as main purpose evaluate the water’s quality of the Ribeirão Lajeado and Rio Sono water sourceand the treated water destinated for the municipal supply of Pedro Afonso City / Tocantins, by laboratorial analysis of water samples with main focus on agrochemicals due to the region be a major producer of sugarcane and soy, and compare the results of the analysis with the MVP’s expressed in the rule 2914/2011 MSand CONAMA 357/2005. The samples were collected in March 2014, in three dinstinct points: P1 –Ribeirão Lajeado, P2 -Rio Sono and P3 –Water’s tank exit (Treated Water). Analysis were performed by an outsourced laboratory –Laboratory Bioagri Located in Piracicaba SP. A visit was made in ETA to evaluate the Treatment Unit’s condition, as well as the operationability of ETA. During the visit, it was found that the water treatment system wasn't operating in the best conditions and the responsibles are not qualified for such functions. The results of the water analysis were in accordance with the portability standards with exception of free residual chlorine that presented a value of 0,07 mg/L, value lower than the minimum which is 0,2 mg/L, and the Aluminium with a value of 0.6489 mg/L, value higher than the MVP that is 0,2 mg/L the others parameters were in accord with the portability standards. The Analyzed parameters in accordance with the standards stabilished in CONAMA 357/2005 for class II, in P1 those who presented values in disagreement were: substances that communicate odor and objectionable solid waste, in P2 Free Residual Chlorine, objectionable solid waste and turbidity, all the other parameters, they comply with the values determined by the legislation in both points. The agrochemicals, focus of this research, shown results in accordance both in treated water and the water source(raw water), such fact might be related with the collect period, time when the crop management happens and the fact that was just one campain.